Advancement and future challenges of metal–organic coordination polymers: A case study of optical sensor for the detection of the environmental contaminants. (30th October 2022) - Dutta, Basudeb; Debsharma, Kingshuk; Dey, Sunanda; Sinha, Chittaranjan
Abstract : Fast industrialization, increasing population, rapid urbanization, and the greediness of creamy layer in the society without the issues of caring the sustainability of ecosystem are the main out of many reasons behind the environmental catastrophe. The ecological balance is disturbed with the noxious materials generated from the uncontrolled use of modern science and technology and also unscientific and unsystematic societal growths. To save the modern civilization, a fast‐track task is the monitoring of the toxic materials for the maintenance of sustainable ecological health and their utilization in a circular economy. Accordingly, optical methods are employed for the detection and estimation of environmental contaminants for immediate monitoring. The stability and structural tunability of the coordination polymeric (CPs) materials make them promising optical sensors for easy, low cost, reliable, selective, and sensitive detection of toxic ions/molecules. The crystallinity, thermal, mechanical, magnetic, and optical stability and flexibility of the CPs play a beneficial role for the accurate and stress‐free recognition of the toxicants. In this review, the recent developments as well as the outlook on the sensing of pollutants at a very low concentration level using CPs as selective and specific sensors by spectro‐fluorometric method are summarized. The progresses and challenges in the fabrication of hybrid materials and understanding their structure property correlations are described with an aim to motivate and facilitate the future researchers to perform research in the area. Abstract : This review article highlights the recent development on the sensing of environmental pollutants using coordination polymers as selective and specific sensors by optical method.